Work Ability Index: validation and model comparison of the Malaysian Work Ability Index (WAI) - Lavasani, Sobhan; Abdul Wahat, Nor Wahiza (Vrije Universiteit e-Publishing, 2016)
Purpose: The study aimed to (1) measure the Work Ability of employees with disability; (2) assess the factor structure of different potential models of Work Ability Index (WAI) for employees with disability; and (3) identify the best factor structure of Work Ability Index for employees with disability in the Malaysian cultural context. Methods: Data was collected using the Work Ability Index (WAI) translated into Malay language. The study sample consisted of 275 employees with physical disability, from both public and private sectors across Malaysia. Descriptive statistics were calculated using IBM SPSS 20 to evaluate the score of each subscale and the cumulative index of Work Ability among employees with disability. Confirmatory factor analysis (CFA) was conducted using IBM SPSS AMOS 21 to assess the factor structure of WAI and evaluate the validity of the proposed models for employees with disability. Results: The WAI scores were 29.5% poor, 35.3% moderate, 28.7% good and 6.5% excellent. In the validation process, a non-orthogonal two dimensional structure was identified. In this model of WAI, the subscales were attributed to two factors: (1) subjective Work Ability factor that consisted of subscales 1, 2 and 7; and (2) health-related Work Ability factor, comprised of subscales 3, 5, 4 and 6. These two factors were positively correlated, which indicates that employees with disability who exhibit positive subjective Work Ability tend to also report positive health- related Work Ability. Conclusion: This study has provided the first Malay version of WAI and has paved the way for future studies on work ability among employees with disability. The WAI translation has been validated among employees with disability and has shown adequate psychometric properties, thus making it suitable to investigate the associations between aspects of work and their impact on the health of employees with disability.